Analisis Pemanfaatan Platfrom Digital dalam Pembelajaran Bahasa Inggsis di SMA N 2 Bangli - Ni Wayan Martini Jovita Yanti; Luh Made Dwi Wedayanthi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
article aims to analyze the use of digital platforms in English language learning in Class XB at SMA 2 Bangli. The background of the study focuses on leveraging technology to enhance learning effectiveness in the digital age. The purpose of the research is to evaluate the application of three digital platforms PowerPoint, Quizizz, and Kahoot and their impact on student engagement and learning outcomes. The method employed is qualitative observation in Class XB to identify how these platforms are utilized in teaching. The findings reveal that PowerPoint facilitates visual presentation of materials, Quizizz enhances student understanding through interactive quizzes and immediate feedback, and Kahoot boosts motivation and participation through game-based quizzes. The implications of this research are that integrating these three digital platforms into English language learning can increase student engagement and teaching effectiveness, offering varied approaches to the learning process. This study is expected to provide guidance for educators on optimizing digital technology for more effective teaching.